How to limit the spillover from the 2021 inflation surge to inflation expectations? - Lena Dräger; Michael Lamla; Damjan Pfajfar (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2022)
By providing numerical inflation projections. Many central banks currently face inflation well above their targets and with that the challenge to prevent spillovers on inflation expectations. We study the effect of different communication about the 2021 inflation surge on German consumers' inflation expectations using a randomized control trial. We show that information about rising inflation increases short- and long-term inflation expectations. This initial increase in expectations can be mitigated using information about inflation projections, where numerical information about professional forecasters' projections seems to reduce inflation expectations by more than policymaker's characterization of inflation as a temporary phenomenon.
Keywords: E31; E52; E58; D84; 330; Short-run and long-run inflation expectations; inflation surge; randomized control trial; survey experiment; persistent or transitory inflation shock